Educators' perceptions of youth mental health: Implications for training and the promotion of mental health services in schools. (February 2017) - Moon, Jungrim; Williford, Anne; Mendenhall, Amy
Abstract: Background: School-based mental health practice holds promise in meeting unmet mental health needs of American children by expanding access to quality mental health care for hard-to-reach populations such as those in rural regions. The purpose of the present study was to address four specific aims: 1) To replicate findings from prior studies regarding educators' perspectives of mental health promotion in school; 2) To extend prior research by examining specific needs for mental health training; 3) To compare the responses between the educators in rural schools and urban schools within the same geographic and political context of a large Midwestern state; and 4) To explore similarities and differences of the educators' perspectives based on participants' roles including administrators, teachers and school mental health providers. Methods: A total of 786 educators including 127 administrators in a large Midwestern state completed a one-time, anonymous online survey. Descriptive analyses were employed to explore the perspectives of educators regarding the current status of mental health promotion in school. Additionally, independent samples t -tests were run to examine the differences in the educators' perspectives based on region (rural vs. urban). Finally, one-way analysis of variance (ANOVA) was used to examine the differences in the educators' perspectives based on participants' roles. Results: Results replicated previous findings, indicating a large percentage of educators reporting a high level of concerns for student mental health needs (93%) and the need for further training in mental health (85%). Mental health disorders, behavior management, and specialized skills such as social skills were identified as the top three areas of need for further training. While no differences were found between educators in urban and rural schools in other topics, significantly more respondents in rural schools (27%) reported that their schools hire mental health professionals as compared to urban schools (13%). The ANOVA results indicated that school-based mental health professionals and administrators are significantly more concerned about students' mental health needs than teachers ( p = 0.000). Conclusion: A majority of participants take students' mental health issues seriously and many feel that current resources and training opportunities could be expanded. An area of future research could be exploring current mental health trainings provided to educators and examine how their specific training needs are addressed. An important strategy to decrease mental health care disparity by geographic region may be statewide initiatives to increase the number of mental health professionals in rural areas. The discrepancy in the level of mental health concerns expressed by teachers and administrators may suggest a need for school-wide initiatives to foster shared commitments to promoting students' mental health across various staff roles. Highlights: Participants take students' mental health issues seriously and feel that current mental health resources and training opportunities could be expanded. Mental health disorders, behavior management, and specialized skills were identified as the top three areas of need for further training. Significantly fewer educators in rural schools reported that their schools hire mental health professionals as compared to those in urban schools. School mental health professionals and administrators were significantly more likely to express concerns about student mental health issues compared to teachers. Administrators were significantly more likely to regard addressing students' mental health issues as a part of their job than teachers.